Recent advances and prospects on retarder application in oilwell cement: A review - Nwaichi, Peter Ikechukwu; Norida, Ridzuan; Nwaichi, Eucharia Oluchi; Umunnawuike, Chika; Agi, Augustine Aja (Elsevier B.V., 2024)
Retarders are used to prevent hydration of oilwell cement by prolonging thickening and setting time for cement slurry application under deep and high-temperature conditions. However, at higher temperature, abnormal gelation and thickening time reversal occur. Hence, an adequate understanding of the factors influencing retarders mechanisms is required for effective application in deep oilwells. Therefore, this review presents vital information on the formulation, mechanism, and factors influencing the application of retarders in oilwell cementing. Herein, the formulation methods were discussed. Thereafter, the different types of retarders and their corresponding mechanisms were pinpointed. Similarly, the factors influencing these mechanisms were revealed. Moreover, the application of retarders in oilwell cementing was reviewed. Finally, the challenges prevalent during the application of retarders in oilwell cementing have unlocked new prospects for research with proffered solutions. Experimental results indicate that the concentration of a retarder is related to the setting time of the cement. Likewise, the consistency of the cement slurry should be less than 30 Bc to ensure that it can be pumped into oilwell. Hence, to achieve a very low consistency, the retarder should be added after the cement past has been prepared rather than premixing with cement (dry blending). But for high-temperature reservoirs (>150 °C), it is advisable to use multiple retarders.